ROADMAP TO ELIMINATE CORRUPTION THROUGH DEVELOPMENT OF INTEGRATED HUMAN - Elizabeth Tiur Manurung (Asia Pacific Fraud Journal, 2016)
Nowadays Indonesia has been overwhelmed by corruption. We all know the impact of corruption is very distressing since it restrains/arrests the economic development, the income is not distributed fairly. In other words, unemployment more and more increases and so does the poverty as well. The focus of this study is to look for some factors to eradicate corruptions, and based on the result of interview and literature study, which used the analytical descriptive method, the conclusion of those factors are come up to the Road map model which is consist of 4 factors, such as: (1) it is necessary to build People with Integrity that will do all their activities with honesty. In this study, people with integrity will produced through morale education; (2) Managing Clear and Integrity business; (3) Building Anti Corruptions Culture; and (4) Legal aspect with clear regulations.